Energetic demands and nutritional strategies of elite cross-country skiers during tou de Ski: A narrative Review - Heikura, I. A.; Kettunen, O.; Garthe, I.; Holmlund, H.; Bucher Sandbakk, S.; Valtonen, M.; Ihaleinen, J. K. (Journal of Science in Sport and Exercise, 2021)
The Tour de Ski (TDS: 6-9 sprint and distance races across 9-11 days) represents the most intense competition series of the cross-country (XC) ski season and is characterized by accumulated stress from consecutive days of high-intensity (~ 85%-160% VO2max) racing, travel, cold temperatures and low to moderate altitude (500-1500 m above sea level). Here, nutritional strategies play a key supportive role for optimized health, recovery and performance. This narrative review aims to provide an evidence-based discussion on the energetic demands of the TDS and recommendations for nutritional strategies to optimize health and performance of XC skiers during and following the TDS. We highlight several challenges that may arise during the TDS, including the following: poor energy availability (EA) due to decreased appetite or a pressure to maintain a low body weight, suboptimal carbohydrate availability due to a failure to replenish muscle glycogen stores across consecutive-day racing and increased risk of illness due to a combination of factors, including high-intensity racing, poor nutrition, sleep, travel and hygiene. We encourage XC skiers to maintain optimal overall EA across the ~ 1.5-week period, ensure high daily carbohydrate availability, as well as the use of strategies to maintain a healthy immune system. In addition, we include practical guidelines on the management of nutrition support prior to and during the TDS. We recognize that many nutritional questions remain unanswered both in the context of elite XC ski racing and specifically for extreme demands like the TDS that should be addressed in future investigations.